AB0655 Are Patients with as Willing to Pay for Treatment with Infliximab?. (10th June 2014) - Webers, C.; Essers, I.; van Tubergen, A.; Braun, J.; Heldmann, F.; Baraliakos, X.; Boonen, A.
Abstract : Background: Use of anti-TNF agents has shown substantial and longstanding improvement in pain and function in Ankylosing Spondylitis (AS). However, these agents are costly, and in some countries the use of these biologicals is questioned because of their budget impact. From a socio-economically point of view, it is of interest how patients value this treatment. A willingness to pay (WTP) is one of the possible approaches to value health gains. Objectives: To investigate the WTP of patients with AS for a treatment with infliximab and explore factors associated with WTP. Methods: Data were used from EASIC open label extension of the ASSERT trial that included 96 European patients with AS who received treatment with infliximab. Demographics, clinical data (including BASDAI, BASFI, BASMI, BAS-G and ASAS20 response) and data on WTP were collected at baseline of EASIC. WTP was assessed with a hypothetical question whether the patient would be willing to pay for the infliximab treatment and, if so, what amount (in euros) the patient would be willing to pay per dose of infliximab. If not willing to pay, the patient was asked to indicate why. To assess the spending power of the patients, patients were asked how much they spend yearly on holidays and on shoes. Finally, patients were asked to indicate what they assumed to be the true price of a year's treatment with infliximab. As the amount patients were willing to pay was non-parametrically distributed with excess of zeros (for patients not willing to pay), a zero inflated negative binomial regression (ZINB) technique was used to investigate factors associated with WTP. A series of models were explored to understand which variables best explain WTP using a forward method. Results: Of the patients included in EASIC, 85 responded to the questions about WTP. Average age was 39.6 years, sixty-seven patients (78.8%) were male and 62 (72.9%) patients had an ASAS20 response. Sixty-three patients (74.1%) were willing to pay for treatment with infliximab. The mean (median) [Interquartile Range (IQR)] amount they were willing to pay was 274.6 (100) euro (IQR: 50-200) per dose. Patients estimated the true price per dose to be on average 2187.3 (2420) euro (IQR: 1500-3000). There were no significant differences with regard to spending power between patients willing to pay and patients not willing to pay. In the willing to pay group, significantly more patients had an ASAS20 response (79.4% vs 54.5%, p-value =0.02), compared to the not willing to pay group. In the multivariable ZINB analysis, ASAS20 response status was invariably associated with willingness to pay as well as with the amount patients are willing to pay, while age was only associated with the amount patients were willing to pay. The country in which the patient is residing (Netherlands) or spending power were also associated in several models with WTP but these results were not always consistent and further exploration was limited by the sample size of the study. Conclusions: 74% of patients with AS are willing to a pay out of pocket contribution for treatment with infliximab. Treatment response and to a lesser extent spending power or country of residence contribute to WTP for infliximab treatment in AS. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5499